Psychosocial and behavioral factors associated with HIV among adolescent girls and young women in DREAMS districts in South Africa: cross-sectional survey - Govender, Kaymarlin; Beckett, Sean; Mukuku, Olivier; Cawood, Cherie; George, Gavin; Khanyile, David; Reddy, Tarylee; Cowden, Richard; Puren, Adrian (Frontiers in Public Health, 2025)
BackgroundHigh HIV prevalence among adolescent girls and young women (AGYW) in South Africa is driven by multiple interacting psychosocial risks. Some of these risks include socioeconomic deprivation, poor educational outcomes, poor mental health, alcohol and drug use which are associated with HIV-infection and sexual risk behavior. This article seeks to deepen our understanding of the role of psychosocial and behavioral factors in the HIV epidemic among AGYW.MethodsA cross-sectional survey (n = 18,296) targeting AGYW aged between 12 and 24 years old was undertaken in four districts in KwaZulu-Natal and Gauteng. The analysis used descriptive statistics and hierarchical multiple binary logistic regressions that were disaggregated by age.ResultsThe mean age is 18 (SD:4) years old. Displaying depressive symptoms had increased odds of being HIV positive among the 15-19-year-old age group of AGYW (AOR: 1.12, 95% CI: 1.05–1.18, p < 0.001). For the 20-24-year olds, increased substance use was associated with a higher likelihood of being HIV positive (AOR: 1.10, 95% CI: 1.03–1.17, p < 0.01) and those who experienced Intimate Partner Violence (IPV) were more likely to be HIV positive (AOR: 1.41, 95% CI: 1.08–1.85, p < 0.05). Our findings indicate a lower prevalence of depressive symptoms in the two adolescent groups (12–15 years old and 15–19 years old) than in the older group (20–24 years old); nevertheless, depressive symptoms increased the likelihood of being HIV positive.ConclusionThis study suggests that HIV interventions are likely to be beneficial if they address individual HIV risk factors such as poor mental health challenges and IPV. However, due to the cross-sectional design, causality or temporal sequencing—particularly in bidirectional relationships such as depression and HIV—cannot be established. Interpretations should therefore be made with caution.